Hoof and foot loads for reindeer (Rangifer tarandus) - Nieminen, Mauri (Rangifer, 1990)
Hoof and foot measurements and body weights were taken from 60 living semi-domesticated reindeer (Rangifer tarandus tarandus L.) (8 female and 13 male calves, 10 young females (age 2 yrs), 9 young males (age 2-3 yrs) and 20 adult hinds) at the Kaamanen Reindeer Research Station during the winter 1988. The outline of the hooves and the feet (hoof + dew claws) from front and hind legs were drawn when pressed down on a hard substrate in a natural position. Measurements were taken also from foot prints of 26 wild forest reindeer (R. t. fennicus Ldnn.) (7 calves, 11 hinds and 8 stags) made on hard snow surfaces in Kuhmo and Salamajarvi national park during 1985-88. Reindeer had bigger hooves and feet on front than on hind legs, and male calves had bigger hooves and feet than female calves. Hoof and foot areas of wild forest reindeer (means 74.6 and 200.3 cm2 for calves, 79.4 and 230.4 cm2 for hinds and 83.6 and 258.6 cm2 for stags) were bigger than those of semi-domesticated reindeer (means, front legs, 60.9 and 165.3 cm2 for calves and 78.9 and 214.1 cm2 for hinds, respectively). There were significant correlations between live weight and hoof areas (r=0.839 and 0.792), between live weight and foot areas in front and hind legs (r = 0.714 and 0.664) and between live weight and foot area when supported by 4 legs (r = 0.726) in semi-domesticated reindeer. Load on ground and foot load in semi-domesticated reindeer when supported by 4 legs were 235 and 85 g/cm2 in calves and 268 and 102 g/cm2 in hinds.